2021
DOI: 10.1021/acsomega.1c01730
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Carbonation of Biomass Ashes in Relation to Their CO2 Capture and Storage Potential

Abstract: Short-term stored, long-term stored, and weathered biomass ashes (BAs) produced from eight biomass varieties were studied to define their composition, mineral carbonation, and CO 2 capture and storage (CCS) potential by a combination of methods. Most of these BAs are highly enriched in alkaline-earth and alkaline oxides, and the minerals responsible for CCS in them include carbonates such as calcite, kalicinite, and fairchildite, and to a lesser extent, butschliite and baylissite. These minerals are a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(107 reference statements)
1
19
0
Order By: Relevance
“…Their formation is a result of both solid-gas and solid-liquid reactions between alkalineearth and alkaline oxyhydroxides and CO 2 during biomass combustion, as well as post-combustion hydration, hydroxylation and carbonation of some minerals by moisture and CO 2 in the air through storage of BAs. It was found that the mineral composition of the short-term stored, long-term stored and weathered BAs is similar; however, there are increased proportions of carbonates and especially bicarbonates in the long-term stored and weathered BAs (Vassilev et al, 2021). The DTA, TG, DSC and evolved CO 2 data show the complete decomposition of carbonates in BAs according to the endothermic effects and mass losses at 600-900 °C (Vassilev et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Their formation is a result of both solid-gas and solid-liquid reactions between alkalineearth and alkaline oxyhydroxides and CO 2 during biomass combustion, as well as post-combustion hydration, hydroxylation and carbonation of some minerals by moisture and CO 2 in the air through storage of BAs. It was found that the mineral composition of the short-term stored, long-term stored and weathered BAs is similar; however, there are increased proportions of carbonates and especially bicarbonates in the long-term stored and weathered BAs (Vassilev et al, 2021). The DTA, TG, DSC and evolved CO 2 data show the complete decomposition of carbonates in BAs according to the endothermic effects and mass losses at 600-900 °C (Vassilev et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…It was found that the mineral composition of the short-term stored, long-term stored and weathered BAs is similar; however, there are increased proportions of carbonates and especially bicarbonates in the long-term stored and weathered BAs (Vassilev et al, 2021). The DTA, TG, DSC and evolved CO 2 data show the complete decomposition of carbonates in BAs according to the endothermic effects and mass losses at 600-900 °C (Vassilev et al, 2021). An example of this decarbonation is illustrated herein for long-term stored and weathered PPA in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the one hand, the individual inorganic phases that comprise the mineral residue can influence the operating parameters of the DC-SOFC. Within the operating temperatures (800-850 • C) of the DC-SOFC, decomposition of the alkali carbonates CaCO 3 or MgCO 3 to MgO and CO 2 may occur [38,39]. The presence of CO 2 , MgO, and CaO can facilitate the solid fuel gasification process in the anode chamber in the DC-SOFC [40].…”
Section: Resultsmentioning
confidence: 99%